Significant Plasma Density Depletion From High‐ to Mid‐Latitude Ionosphere During the Super Storm in May 2024 - Yaqi Jin; Daria Kotova; Lasse B. N. Clausen; Wojciech J. Miloch (Geophysical Research Letters)
Abstract We demonstrate the global response of the ionosphere to the geomagnetic super storm on 10–11 May 2024. The in situ observations from the Swarm spacecraft show a rapid depletion of plasma density in the dawn and dusk sectors following the storm. The in situ data are further complemented by the ground‐based total electron content maps. Both the in situ and the ground‐based observations show significant depletion of electron density during the super storm in regions above 50° magnetic latitude. The density depletion originates from a polar hole in the morning high latitude sector. It is suggested that the strong convection speed under substantial solar wind forcing leads to chemical composition changes and rapid recombination in the ionosphere. The region of depleted plasma density is not confined to the polar cap but expands to auroral and mid‐latitude regions. The depleted plasma density lasts for about 3 days before it recovers to the pre‐storm levels.